Can Table Tennis Extend Lifespan? An Analysis of Its Impact on Physical Health, Brain Function, and Mental Well-being - Marta, Patrycja; Ossolińska, Agata; Huzarski, Filip; Ferfecka, Gabriela; Pawełek, Klaudia; Stolarska, Lucyna; Rosa-Bończak, Magdalena; Morawiecka, Natalia; Carlton, Olivier; Weronika Kłosowicz, (Journal of Education, Health and Sport, 2025)
Introduction: In the context of an aging society, the importance of physical activity as a key element in supporting health and improving quality of life is growing. Table tennis, a sport played by millions worldwide, combines aerobic, coordination, and strategic exercises, making it unique in terms of its impact on physical and mental health. Aim of the study: Analyze the impact of regular table tennis play on life expectancy and physical, cognitive, and mental well-being. Materials and Methods: This analysis is based on a detailed review of studies and information related to table tennis, sourced from PubMed and Google Scholar databases. Conclusions: The literature review indicates that table tennis offers numerous health benefits, including improved body composition, enhanced coordination, reduced risk of cardiovascular disease, and better motor functions. The sport stimulates cognitive functions such as reflexes, anticipation, and memory, with studies confirming its positive effects on individuals with Parkinson's disease, dementia, or mild cognitive impairment. Table tennis also enhances mental well-being by reducing stress levels and improving quality of life through social integration and satisfaction from the game. The collected data suggest that table tennis should be included in rehabilitation programs and health promotion activities for all age groups. Its universal accessibility and health benefits—physical, cognitive, and social—highlight its potential as a vital form of physical activity to address contemporary health challenges.